Khan Academy Videos in Chinese: A Case Study in OER Revision - Rao, Allen; Hilton III, John; Harper, Sarah (International Review of Research in Open and Distributed Learning, 2017)
Over the past decade, great progress has been made in improving the quality and availability of Open Educational Resources (OER). OER proponents often discuss the ability for users to revise and remix OER to make them more suitable for local contexts; however, much OER goes unmodified. This note from the field examines the efforts of NetEase Online Open Courses, a Chinese organization, to take more than two thousand Khan Academy videos and translate them into Chinese. We provide background on this initiative and also analyze site metrics to determine what type of use these derivative OER have received.